PREVENTIVE ENDODONTIC CONSIDERATION ON PULP AND PERIAPICAL TRAUMATISM IN FIXED FINAL RESTORATION: PERTIMBANGAN ENDODONTI PREVENTIF TERHADAP TRAUMA PULPA DAN PERIAPIKAL DALAM RESTORASI AKHIR CEKAT - Dennis; Trimurni Abidin (Dentika: Dental Journal, 2010)
The success of fixed restoration preparation relies on several factors i.e. preparation of abutment tooth which must consider pulp-dentin complex and degree of occlusal traumatism. The thinner remaining dentin thickness during abutment preparation, the easier for inflammation and microbial invasion to occur. Inflammation of the pulp with release of inflammatory mediators such as prostaglandin, interleukin and microbial invasion through dentinal tubules played an important role in bone resorption and periapical lesions. This article was aimed to find out the treatment for periapical abscess resulted from porcelain-fused-to-metal (PFM) fixed restoration on maxillary left canine. A 56 year-old male patient was referred to clinic at Department of Conservative Dentistry, Faculty of Dentistry University of Sumatera Utara. He had a bridge from 23 to 26 on his maxillary left side. He felt discomfort in his maxillary left canine. Radiographic evidence showed radiolucency at apical area and clinical evaluation revealed periapical abscess at gingival mucosa of the tooth. Patient felt tenderness to percussion and palpation. Sequence of the treatment procedures was undertaken as follows: trephination and abscess drainage, root canal treatment using step back technique, obturation using lateral condensation method and eventually restored with composite resin using silane as coupling agent. At two-month evaluations, patient had no dental complaint, no tenderness to percussion and palpation as well as absence of clinical and radiographic periapical abscess. As conclusion, root canal treatment following hermetic root canal obturation and proper final restoration for periapical abscess resulted from PFM fixed restoration will determine the success of the treatment outcome.